(untitled) (Revista de Investigaciones Universidad del Quindío, 2014)
In this study, an evaluation of the susceptibility to water erosion of soils in the central section of the Las Piedras river basin, where areas devoted to pasture and crops predominate was made. The basic tools for the research were mini rainfall simulators, operating under the drip system, supported by the analysis of soil physical and chemical properties and map databases. The soil samples and surface runoff were analyzed in the laboratory at University of Cauca following the soil and water analysis procedures of IGAC and Standard Methods. Analysis of these soils reported a sandy-loam texture, field humidity between 39-51%; pH from 4.8 to 5.5, corresponding to acid soils, with a CO percentage above 5% and CEC between 36-46 meq/100cc. The quantity of eroded soil ranged from 0.43 to 7.8 g for crops and 0.3 to 5.78 g in pasture at an intensity of 100 mm h-1, showing the influence of rainfall in the susceptibility to water erosion physical and chemical characteristics of the soil and the different land uses.